2023
DOI: 10.17843/rpmesp.2023.401.12491
|View full text |Cite
|
Sign up to set email alerts
|

Rinitis alérgica asociada al grado de compromiso pulmonar por COVID-19 en pacientes de un hospital general peruano

Abstract: Objetivos. Evaluar la asociación entre rinitis alérgica y el grado de compromiso pulmonar en pacientes con COVID-19 y evaluar las frecuencias de las variables principales. Materiales y métodos. Se realizó un estudio de tipo observacional, transversal y analítico mediante la revisión de historias clínicas de pacientes atendidos en el Hospital Nacional Cayetano Heredia entre el año 2020 y 2021 con diagnóstico de COVID-19. Se determinó el antecedente de rinitis alérgica, y el compromiso pulmonar se evaluó mediant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
(66 reference statements)
0
3
0
3
Order By: Relevance
“…We thank the authors of the letter for the interest and time dedicated to reviewing our article, which aimed to evaluate the association between the presence of allergic rhinitis and the degree of pulmonary involvement in patients with COVID-19. This research, with results that we consider to be preliminary, found that the history of allergic rhinitis represented a decrease of 30% in the severity of COVID-19 in hospitalized patients according to the tomographic score (TS) 1 .…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…We thank the authors of the letter for the interest and time dedicated to reviewing our article, which aimed to evaluate the association between the presence of allergic rhinitis and the degree of pulmonary involvement in patients with COVID-19. This research, with results that we consider to be preliminary, found that the history of allergic rhinitis represented a decrease of 30% in the severity of COVID-19 in hospitalized patients according to the tomographic score (TS) 1 .…”
mentioning
confidence: 75%
“…Unfortunately, as was also pointed out in our article, the information and variables that were included in the study were those that were found in the medical records, therefore, we were not able to include other variables that may have contributed to explain the association. Besides, although these variables could be other respiratory parameters as the authors pointed out, the increase of TS is associated with increased mortality, disease severity and can predict hospital stay and the need for intubation of infected patients 1 . Thus, we consider that this variable could be relevant for our research, in which we sought to estimate, in an exploratory manner, an association of interest.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We interestingly reviewed the published article by García-Gallo et al . 1 and consider that it is important to mention some aspects that are not clearly described in the limitations.…”
mentioning
confidence: 99%
“…Sr. Editor, al revisar con interés el artículo recientemente publicado de García-Gallo et al . 1 es importante mencionar algunos aspectos que no están claramente descritos en las limitaciones.…”
unclassified